The Effect of Tax Planning Aspects and Tax Awareness to the UMKM Taxpayer Compliance (Study on Sme Tax Mandatory in Karawaci Area of Tangerang City) - Herman Herman; Waluyo Waluyo (DINASTI RESEARCH, 2021)
The purpose of this study is to examine how much influence the formal aspects and material aspects of tax planning, tax awareness on tax compliance. The analytical method used is quantitative and analytic statistics used, namely multiple linear regression analysis. The population of this research is the SME taxpayers in the Karawaci region of the city of Tangerang. The sampling technique used is probability sampling. The results showed that the formal aspects of tax planning and the material aspects of tax planning affect the compliance of taxpayers, while tax awareness does not affect the compliance of SME taxpayers in the Karawaci region of Tangerang.